Regulation of Escherichia coli sigma F RNA polymerase by flhD and flhC flagellar regulatory genes. - Arnosti, D N (1990)
The sigma F RNA polymerase has been characterized biochemically and is known to transcribe several flagellar genes in Escherichia coli. It was found that while the flagellar regulatory genes flhD and flhC are required for sigma F activity, the sizes of their corresponding gene products are inconsistent with their encoding sigma F itself.